Clinico-Radiological Factors Affecting Outcome of Supratentorial Spontaneous Intracerebral Hemorrhage: A Single Institute Experience - Yogi, Nikunj; Thulung, Suraj; Sharma, Prakash (Nepalese Journal of Radiology, 2019)
Introduction: Intracerebral bleeds are the second most common cause of stroke. The initial consciousness level and progressive deterioration and various radiological parameters like hematoma volume, its expansion, mass effect and location has been implicated with poor outcomes of Intracerebral Hematoma (ICH) regardless of the management methods. In this study we aimed to study various clinical and radiological parameters associated with outcome of spontaneous supratentorial ICH. Methods: This prospective study was carried out in 89 patients of spontaneous supratentorial ICH admitted to National Institute of Neurological and Allied Sciences, Nepal in between January 2015 to December 2015 to assess various parameters associated with its outcome. Outcome of the patients were assessed against various clinic-radiological and demographic variables using chi square test and student’s t test respectively for categorical and continuous variables using IBM SPSS 20 software. Results: Glasgow Coma Scale (GCS) (p=0.00), size of hematoma (p=0.034), presence of midline shift (0.000) and presence of intraventricular hematoma (p=0.020) were found to have statistically significant difference when compared in between good and poor outcome group. Conclusion: GCS at admission, size of hematoma, midline shift in cerebral tomography scan (CT scan) and presence of intraventricular hemorrhage (IVH) were significantly associated with outcome of spontaneous Supratentorial ICH.